Albert Noguera Fernández, El asalto a las fronteras del derecho. Revolución y Poder constituyente en la era de la ciudad global. - Mondaca Garay, Daniel (EUNOMÍA. Revista en Cultura de la Legalidad, 2025)
The Assault on the Borders of Law... (Trotta, 2023) is a book analyzing the ontological consubstantiality between the modern constitutional paradigm and the phenomenon of constituent power as an event of normative destruction and creation. The author argues that the transformations brought by the global economy to the form of the State have resulted in a weakening of the normative effectiveness of constitutions, and consequently, in a decline of the constituent discourse. Noguera proposes the concept of "borderism" as a new analytical framework to examine normative transformation in the current context of the deterritorialization of law.